It’s rather half of that or double of that
-2(2b-3)
Multiply the bracket by -2
Whenever multiplying a -negative number with a -negative number= + positive number.
(-2)(2b)(-2)(-3)
-4b+6
Answer: -4b+6
Answer:
z = 7
Step-by-step explanation:
Based on the midsegment theorem of a triangle, the length of the midsegment of the triangle (z) = ½ of the length of the 3rd side of the triangle (14)
Thus:
z = ½(14)
z = 7
Answer:
B
Step-by-step explanation:
Answer:
not a function - it does not pass the vertical line test.
Step-by-step explanation: